2018
DOI: 10.4103/tjo.tjo_69_18
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab or laser for aggressive posterior retinopathy of prematurity

Abstract: PURPOSE:The purpose of this study was to report the rate of reactivation and structural outcome, after the laser or bevacizumab treatment for aggressive posterior retinopathy of prematurity (APROP).METHODS:Retrospective chart review was conducted on consecutive infants with APROP treated with (1) laser or (2) bevacizumab, followed by fluorescein angiography and prophylactic laser to the persistent avascular retina.RESULTS:Thirty-six eyes of 19 patients were included in this study. The mean gestational age was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 47 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…The recurrence rate is higher in type 1 ETROP with RBZ as compared to BVZ,[ 38 ] and almost similar recurrence in APROP with either of the two drugs. [ 39 ] The majority of the respondents of the current survey (46.5%) preferred weekly follow-up. However, around one-third (36.3%) of respondents decided their follow-up schedule based on the disease severity.…”
Section: Discussionmentioning
confidence: 98%
“…The recurrence rate is higher in type 1 ETROP with RBZ as compared to BVZ,[ 38 ] and almost similar recurrence in APROP with either of the two drugs. [ 39 ] The majority of the respondents of the current survey (46.5%) preferred weekly follow-up. However, around one-third (36.3%) of respondents decided their follow-up schedule based on the disease severity.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent study, Mintz-Hittner showed reactivation in 100% of eyes with APROP [17] while Blair et al found 41% reactivation in APROP eyes in their study. [18] This difference in reactivation may be because of higher levels of VEGFs in APROP eyes. Because of late reactivation up to 69 weeks+ after anti-VEGF treatment, longer-term follow-up is required.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to thank Dr. Samanta for interest in our recent manuscript regarding aggressive posterior retinopathy of prematurity (APROP). [1]…”
mentioning
confidence: 99%